2018
DOI: 10.14203/risetgeotam2018.v28.835
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary Facies and Hydrocarbon Reservoir Potential of Sand Flat in the Upper Part of Tapak Formation in Banyumas Area, Central Java

Abstract: The upper part of Tapak Formation in Kali Cimande consists of alternating sandstones, siltstone and mudstone. The alternating sequence showed a fining and thinning upward bedding pattern. The facies association of the alternation built up by sand flat facies, which characterized by medium sandstone, moderate sorted, with cross-lamination sedimentary structures and mostly on the top of sandstone layer found a bioturbation trace fossils (Skolithos). Mixed flat facies, which is characterized by an alternation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Ma'arif [5] studied the lower part of the Tapak Formation and identified it was deposited as part of the deep sea levee and middle fan channel. The detailed information and history of hydrocarbon exploration in the Tapak Formation is still not adequate [4]. This study on the limestone of the Tapak Formation will provide more information about the petroleum system in Central Java, Indonesia.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ma'arif [5] studied the lower part of the Tapak Formation and identified it was deposited as part of the deep sea levee and middle fan channel. The detailed information and history of hydrocarbon exploration in the Tapak Formation is still not adequate [4]. This study on the limestone of the Tapak Formation will provide more information about the petroleum system in Central Java, Indonesia.…”
Section: Introductionmentioning
confidence: 98%
“…Amin [3] identified that the depositional environment of Tapak Formation ranged from tidal to deep marine. Based on sedimentary facies and microfossil content, Rizal [4] identified that the upper part of the Tapak Formation is characterized by alternating sandstone, siltstone, and mudstone, with fining and thinning upward sequence. Rizal [4] also identified that the sandstone of the upper part of the Tapak Formation could play as reservoir potential, as this sandstone has 10 to 15% porosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local people call this oil seep as "oli", probably came from Dutch language "olie" which means oil. Several authors had reported and published studies regarding to this oil seep (Mulhadiyono, 1973;Subroto, et.al., 2005;Armandita, et.al., 2009, Rizal, et. al., 2018.…”
Section: Introductionmentioning
confidence: 99%
“…On the island of Java itself, starting from West Java to East Java, there are very many turbidite deposits during Miocene to Pliocene. Some of them in West Java and Central Java have been investigated by Rizal et al (2016Rizal et al ( , 2017 and Praptisih et al (2012) explain the sedimentation facies of turbidite deposits aged Mio-Pliocene, and Rizal (2018) explain the relationship the relationship of turbidite deposits with hydrocarbon reservoir potential. Deep sea sediments generally have the potential for hydrocarbon systems, as they have been proven in the Kutei Basin, Brunei, Tarakan, North Sumatra, East Java, and Palawan Basin (Kusumastuti et al, 2001) and the Bintuni Basin (Nugrahanto et al, 2001).…”
Section: Introductionmentioning
confidence: 99%